Reasons for non-participation in a primary care-based physical activity trial: a qualitative study. Issue 5 (23rd May 2016) - Attwood, S; Morton, K L; Mitchell, J; Van Emmenis, M; Sutton, S
Abstract : Objectives: To explore reasons for non-participation in a primary care-based physical activity trial and understand how these may contribute to recruitment of non-representative research samples. We also aimed to elicit non-participants' own recommendations for enhancing trial uptake in primary care. Design: Semistructured telephone interviews with non-participants to a randomised controlled trial of a very brief intervention for promoting physical activity conducted in primary care (the Very Brief Interventions trial), with thematic analysis of interview transcripts. Setting: 5 general practice (GP) surgeries in the East of England, UK. Participants: Interviews were completed with 10 female and 6 male non-participants of white ethnicity and aged between 40 and 71 years. 13 of the 16 interviewees were either active or moderately active according to the GP Physical Activity Questionnaire (GPPAQ). Results: Interviewees discussed a range of reasons for non-participation. These included beliefs surrounding the personal relevance of the trial based on preconceptions of intervention content. Many interviewees considered themselves either sufficiently active or too functionally limited to increase activity levels further, so rendering participation pointless in their view. Other identified barriers included a lack of free time, for trial participation and for increasing physical activity, and dissatisfaction with appointment scheduling systems in place at GP surgeries. Interviewees questioned the appropriateness of primary care as a context for delivering interventions to promote physical activity. In general, interviewees were positively disposed towards the idea of trial participation, especially if personal benefits are made salient, but suggested that interventions could be delivered in a different setting such as the internet. Conclusions: To increase participation in physical activity promotion trials conducted in primary care, the content of invitation materials and procedures for contacting potential participants require reconsideration. Specific recommendations include streamlining intervention materials and enhancing their relevance to the health concerns of invitees. Trial registration number: ISRCTN72691150; Pre-results.